KEANEKARAGAMAN UDANG AIR TAWAR (DECAPODA: CARIDEA) DI SUNGAI BATUSUYA, SULAWESI TENGAH, INDONESIA - Diky Dwiyanto; Fahri Fahri; Annawaty Annawaty (Fakultas Biologi | Universitas Jenderal Soedirman, 2018)
Sulawesi is one of the four Greater Sunda Islands characterized by rivers and lakes habitats of freshwater shrimps and prawns with a high degree of endemism. The freshwater shrimp and prawns diversity in the Batusuya river of Donggala is less studied compared to the ancient lakes in the Central Sulawesi area. This study aimed to determine the diversity of freshwater shrimp and prawns of the Batusuya river. The sample was collected in November 2016 using tray net. The study site divided into three sampling stations based on the type of habitat. Nine species of freshwater shrimps and prawns were found, i.e., Macrobrachium australe, M. esculentum, M. horstii, M. lar, M. placidulum, Caridina brevicarpalis, C. gracilipes, C. weberi, and Atyopsis spinipes. Six species were found in all localities including Macrobrachium australe, M. esculentum, M. horstii, M. lar, C. brevicarpalis, and C. gracilipes, while M. placidulum, C. weberi, and A. spinipes were not found in all stations. The highest diversity index (H') was found in the station III indicated freshwater shrimps and prawns favored the environmental conditions of this station. The highest measure of species richness (R) was found in the station I and presumably related to the life cycle of freshwater shrimps and prawns which is amphidromous. The occurrence of nine species of freshwater shrimps and prawns along the Batusuya river indicated the environmental condition of the stream was suitable for most freshwater shrimps and prawns, and the Macrobrachium australe was found as the most abundant species.